ANALYSIS OF TEACHER'S STYLE IN TEACHING MATHEMATICS AT CLASS IV SDN 005 PENDALIAN IV KOTO ROKAN HULU REGENCY - Risda Novianti; Lazim N; Syahrilfuddin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
Teaching style is a very important aspect that should be considered by teachers and educators since it is the key to success in creating a more interesting and interactive learning environment. The purpose of this study is to describe the teaching style applied by the teacher in teaching mathematics in Class IV at SDN 005 IV Koto, Rokan Hulu Regency. The subject in this study was a teacher of grade IV at SDN 005 Pendalian IV Koto. The research method used in this study was descriptive, with data collection techniques through observation and documentation. The results showed that the fourth grade teacher of SDN 005 IV Koto applied classical, technological, personalized, and interactional teaching styles in teaching mathematics. The classical teaching style was very dominantly applied, whereas the technological, personalized, and interactional teaching styles were not implemented properly. Basically, the teacher must sustainably improve their teaching style to adapt to the demands of current learning, where students have an active role and dominate learning with the teacher as a facilitator.